Grand Narrative Pemberantasan Korupsi dalam Wacana Konflik Sepak Bola di Media Cetak - Afdal Makkuraga Putra (Jurnal Aspikom)
Eradication of corruption has been a grand narrative since the early of reformation era. Mass media became part of the preservation of the grand narrative. Grand narrative is the main narration which becomes basis and universal character since it can be used as standard to measure and assess other narratives. This study analyzes grand narrative of corruption eradication in Indonesia soccer conflict in print media by using critical discourse by Norman Fairclough as research method. The result shows that media preserved grand narrative of corruption eradication through image projection of corruptors as common enemy. The spread of anti-corruption information through mass media carried out continuously and sustainably is a manifestation of the commitment to fight corruption. Information provided by media does not only explains the state’s loss but up to the development of its completion.